Implementasi P5PPRA melalui Gerakan Sekolah Menyenangkan di Madrasah Tsanawiyah - Alfiah Khoiriyah Siregar; Zulhammi; Hamdan Hasibuan (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
The Pancasila Student Profile Strengthening Project and Rahmatan lil ‘Alamin Student Profile (P5-PPRA) is an educational initiative designed to provide meaningful learning experiences through the contextual integration of knowledge, values, and character building. This research and development (R&D) study aims to: (1) develop a P5-PPRA project learning module by integrating the School Fun Movement approach at the Islamic Junior High School level, and (2) test the feasibility, practicality, and effectiveness of the developed module. This study adopted the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Expert validation was conducted by three experts (content and design), while the practicality test involved five Islamic Religious Education teachers. The expert validation results show that the module was rated highly feasible in terms of content and design. The practicality test by PAI teachers also placed the module in the very practical category. These findings indicate that the developed module has the potential to be used effectively in implementing character-based learning that reflects the values of Pancasila and the principles of Rahmatan lil ‘Alamin. Theoretically, this study contributes to enriching the literature on the application of the ADDIE model to design learning tools based on cultural context and character. Practically, this module provides an alternative teaching tool that can be adapted by teachers, especially PAI teachers, in the learning process across various educational institutions.